Scabies in Indonesia: Epidemiology and Prevention - Reqgi First Trasia (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2020)
Scabies is still a health problem in the world, including Indonesia. The World Health Organization (WHO) in 2017 stated that scabies is included in the Neglected Tropical Disease (NTD) which requires large-scale control. In Indonesia, according to data from the Ministry of Health Republic of Indonesia the prevalence of scabies in 2017 is 6% of the total population in Indonesia. Discussion on the incidence and prevention of scabies from various regions in Indonesia so far is still not comprehensive. This review will provide an overview related to epidemiology and preventive measures against scabies so that scabies cases in Indonesia can be controlled properly